Responsabilidade social empresarial nos hospitais privados do Distrito Federal - Martins, Rodolpho Freire (2013)
This paper explores and seeks to understand the why of the Federal District Hospitals engage in practices of Corporate Social Responsibility. It began with the lifting of the concept of CSR, analyzing what exists on the subject, then a specific definition was elaborated qualitative research interviews with senior management and with the comforting view of employees and the community in which the hospital is inserted. The market and society pressure companies with regard to social responsibility and these changes directly impact the organization, in its objectives and its activities in the society. Much of the policies and actions of Corporate Social Responsibility these hospitals based on not so clear visions about what Social Responsibility as a response as a result of pressures and obligations. But there is in some cases a proactive action in response fundamental social and business strategy generating benefits for both the enterprise and society. This study reveals that private hospitals in the Federal District have policies or actions and social responsibility, due to inherent activity to be healthy and have a strong legislation and certifications that these companies charge such attitudes.